2019
DOI: 10.1158/1055-9965.epi-18-1083
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Sterol-27-Hydroxylase (CYP27A1) Expression in Relation to Cholesterol Synthesis and Vitamin D Signaling and Its Association with Lethal Prostate Cancer

Abstract: Background: Higher intratumoral cholesterol synthesis is associated with a worse prognosis in prostate cancer. The vitamin D-regulated enzyme sterol-27-hydroxylase (CYP27A1) converts cholesterol to 27-hydroxycholesterol, potentially lowering intracellular cholesterol levels. We hypothesized that low CYP27A1 expression is associated with high cholesterol synthesis, low vitamin D signaling, and higher risk of lethal prostate cancer.Methods: In 404 patients from the prospective prostate cancer cohorts within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Recent research indicated that vitamin D inhibits cell proliferation and maintains the stem cell phenotype by increasing several stemness-related gene expressions (Fernández-Barral et al 2020). Besides, one of the main vitamin Drelated genes, CYP24A1 was found to be negatively associated with the prognosis of prostate cancer (Khan et al 2019). Therefore, vitamin D-related genes are critical in the development and progression of carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research indicated that vitamin D inhibits cell proliferation and maintains the stem cell phenotype by increasing several stemness-related gene expressions (Fernández-Barral et al 2020). Besides, one of the main vitamin Drelated genes, CYP24A1 was found to be negatively associated with the prognosis of prostate cancer (Khan et al 2019). Therefore, vitamin D-related genes are critical in the development and progression of carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, if an enhancing effect of 27OHC on primary breast cancer is dependent upon its binding to estrogen receptors, the oxysterol exerted promotion of lung metastases seems to not involve ER [15]. Besides the epidemiological studies to date available that suggest a significant correlation between high 27OHC levels and reduced risk of breast cancer [20,21], one should consider that all reports related to human prostate cancer consistently indicate a protective and not a detrimental role of 27OHC as to tumor progression and growth [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of CYP27A1 was again found lower in advanced stage carcinomas, with high Gleason score. Importantly, the clinical cases from both cohorts with higher risk of developing metastasis and eventually death were consistently showing a relatively low expression of the 27OHC synthetic enzyme in the neoplastic tissue [29].…”
Section: Ohc and Prostate Cancermentioning
confidence: 92%
“…Recent research indicated that vitamin D inhibits cell proliferation and maintains the stem cell phenotype by increasing several stemness-related gene expressions ( Fernández-Barral et al, 2020 ). Besides, one of the main vitamin D-related genes, CYP24A1 was found to be negatively associated with the prognosis of prostate cancer ( Khan et al, 2019 ). Therefore, vitamin D-related genes are critical in the development and progression of carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%